ANALISIS YURIDIS PERATURAN MENTERI KEUANGAN (PMK) NO. 130/PMK.010/2012 TENTANG PENDAFTARAN FIDUSIA BAGI PERUSAHAAN PEMBIAYAAN - Widaningsih, Widaningsih (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2016)
Forced withdrawal of vehicles for reasons of delinquent installments by debt collectors as officers of financial institutions is a common incident from various press and experiences in the community. On the basis of legal certainty for companies and consumer financing in connection with the implementation of the fiduciary transaction on August 7, 2012 which then rises Minister of Finance Regulation No. 130 / PMK.010 / 2012 On Registration Fiduciary Company For Consumer Financing Financing Conducting For Motor Vehicles with Imposition Fiduciary. According to Article 1 PMK No. 130 / PMK.010 / 2012, finance companies doing consumer financing for motor vehicles with the imposition of fiduciary must register fiduciary referred to in Fiduciary Registration Office, appropriate legislation governing the fiduciary (article 1).The fiduciary guarantee registration obligation applies to finance companies that do:a) The motor vehicle consumer financing based on Islamic principles;b) and / or consumer financing vehicles whose financing comes from pembiayaanpenerusan (channeling) or cofinancing (joint financing).With the release of this rule, all companies must register fiduciary financing for each transaction financing. Therefore, Article 2 PMK No. 130 / PMK.010 / 2012, states that the Company shall register fiduciary Financing in Fiduciary Registration Office no later than 30 (thirty) calendar days from the date of consumer financing agreement.Methods This study uses normative